High-density polyethylene superfine fiber tarpaulin and preparation method and application thereof

CN119221204BActive Publication Date: 2026-10-20ZHONGYUAN ENGINEERING COLLEGE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411446582.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2026-10-20
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

遗憾的是,虽然现有以HDPE超细纤维网制备的非织造产品具有高强度和优异屏蔽性,但也表现出手感差、“塑料感”强的质感,而水刺非织造固网工艺是利用高速水射流促使纤维运动而相互穿插缠结的柔性固网技术,能够服务于HDPE超细纤维网固结

Benefits of technology

1、本申请以高密度聚乙烯(HDPE)为原料,将HDPE超细纤维网经过水刺固结工艺后,制备一种HDPE超细纤维材料;基于所制备的HDPE超细纤维网直径分布在1~6 μm特点,在水射流冲击下可以形成均匀、致密的稳定超细纤维非织造结构。调整水针能量和单位面积质量,可以实现孔隙率在82.7%~85.9%和模态孔径在6~8 μm内的可调可控,从而实现力学性能的提升;110g/m2样品在2821.9 kJ/m2的水射流冲击下,样品纵向和横向拉伸断裂强力分别为217.8 N和168.0 N。得益于HDPE纤维低表面能和HDPE超细纤维水刺固网所形成的非织造结构,样品具有高的耐静水压为6695.7Pa和良好的透气率和水蒸气透过率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221204B_ABST
    Figure CN119221204B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of textile materials, and relates to the preparation of high-performance fibers, in particular to a high-density polyethylene ultrafine fiber tarpaulin and a preparation method and application thereof. A high-density polyethylene (HDPE) ultrafine fiber material is prepared by using a water jet consolidation HDPE ultrafine fiber web method. The sample exhibits a dense ultrafine fiber non-woven structure, and is a flexible porous material with a porosity of 82.7% to 85.9% and a modal pore size of 6 to 8 μm. The tensile breaking strength and the bursting strength are respectively increased to 218.0 N and 301.3 N as the water needle energy increases, and the flexibility is higher than 80. The hydrostatic pressure is increased to 6695.7 Pa as the sample unit area mass is increased to 110 g / m 2 , the air permeability and the water vapor transmission rate are 48.3 mm / s and 2321.2 g / (m 2 ·24h). The sample has high strength, softness and waterproof and air permeability, and can be used as a tarpaulin for outdoor sports, material storage and safety protection performance improvement of military materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of textile materials and relates to the preparation of high-performance fibers, specifically a high-density polyethylene microfiber tarpaulin, its preparation method, and its application. Background Technology

[0002] As a physical barrier between supplies and the external environment, tarpaulins possess a combination of aesthetic appeal, protective function, and moisture and heat regulation. They are used not only for personal outdoor protection but also for collective protection such as supplies storage, sports facility security, and military equipment camouflage and concealment, making them an important component of safety and protective equipment. Traditional tarpaulins are mostly made of coated modified fiber materials and multi-layered composite materials, possessing high mechanical strength and excellent waterproof properties. However, traditional tarpaulins are often dense and thick, exhibiting poor flexibility, low fit, and portability in practical applications, greatly limiting their use in personal protection and covering high-value, irregularly shaped targets. Therefore, developing high-strength, lightweight fiber materials has become a common research hotspot in the fields of sports, safety protection, and functional textiles.

[0003] Flexible fiber materials prepared by nonwoven processes such as electrospinning, meltblowing, and bicomponent spunbond-hydroentanglement possess the unique dense structure of microfiber nonwoven materials, exhibiting excellent shielding properties and attracting widespread attention in the industry. However, these processes suffer from industry challenges such as low production efficiency and poor mechanical properties, making it difficult to meet the commercial application requirements of high-strength, lightweight tarpaulins. Current nonwoven web-forming technology for microfiber materials has the advantages of wide availability of raw materials (such as high-density polyethylene and polypropylene) and high production efficiency, making it suitable for large-scale production of microfiber webs. High-density polyethylene (HDPE), as a commonly used polymer raw material for preparing microfiber webs, possesses excellent thermal stability and moldability, and is widely used in the field of nonwoven products. Unfortunately, although existing nonwoven products made from HDPE microfiber webs have high strength and excellent shielding properties, they also exhibit poor hand feel and a strong "plastic" texture. Hydroentangled nonwoven web-forming technology, which utilizes high-speed water jets to promote fiber movement and interweaving, is a flexible web-forming technology that can serve the consolidation of HDPE microfiber webs. This application explores in-depth methods for the hydroentanglement of HDPE microfiber webs and the properties of HDPE hydroentangled microfiber materials. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention proposes a high-density polyethylene (HDPE) microfiber tarpaulin, its preparation method, and its applications.

[0005] The technical solution of this invention is implemented as follows: A method for preparing HDPE microfiber tarpaulin, comprising the following steps: The method for forming HDPE microfiber web: HDPE chips are heated, softened, and melted into a polymer melt, which is then fed together with a solvent into a mixing vessel at a temperature of 205 ℃ and a pressure of 20 MPa to prepare a spinning solution with a mass fraction of 15%-25%. The solvent is prepared by mixing dichloromethane (mass ratio 50%-80%) and methanol (mass ratio 20%-50%) in a specific mass ratio. The spinning solution is sprayed into an atmospheric pressure environment through a depressurization chamber. During this process, the solvent evaporates instantaneously to form HDPE microfibers. Under the action of a deflector plate, the HDPE microfibers are split, turned, and deposited on a receiving screen to form an HDPE microfiber web.

[0006] Hydroentangling of HDPE microfiber materials: The HDPE microfiber web is hydroentangled using a hydroentangling web system (SC-600, Changzhou Xinrenli Textile Equipment Co., Ltd.). The HDPE microfiber web passes through multiple hydroentangling heads and is formed into HDPE microfiber material under the impact of water jets.

[0007] The parameters for the above-mentioned hydroentanglement consolidation are: main needle pressure 6-10 MPa, feeding speed 3 m / min, and water needle energy 1699.3-8299.7 kJ / m. 2 .

[0008] Furthermore, the energy of the water needle is 2105.9-8299.7 kJ / m³. 2 .

[0009] The high-density polyethylene microfiber tarpaulin prepared by the above method.

[0010] The aforementioned high-density polyethylene microfiber tarpaulin has a porosity of 82.7%-85.9%, a modal pore size of 6-8 μm, and an areal density of 90-110 g / m³. 2 .

[0011] The aforementioned high-density polyethylene microfiber tarpaulin has a water contact angle of 140±5°, a hydrostatic pressure resistance of >4500 Pa, a softness score of >80, a reflectivity of 94.3%, and also has an outdoor radiative cooling capacity that is 11.2 ℃ higher than that of pure cotton cloth.

[0012] The above-mentioned high-density polyethylene microfiber tarpaulin is used in the preparation of outdoor sports, material storage and military supplies.

[0013] The present invention has the following beneficial effects: 1. This application uses high-density polyethylene (HDPE) as raw material and prepares an HDPE microfiber material by hydroentangling and consolidating an HDPE microfiber web. Based on the characteristic that the prepared HDPE microfiber web has a diameter distribution of 1~6 μm, it can form a uniform, dense, and stable microfiber nonwoven structure under water jet impact. By adjusting the water jet energy and unit area mass, the porosity can be adjusted and controlled within 82.7%~85.9% and the modal pore size within 6~8 μm, thereby improving the mechanical properties; 110 g / m² 2 The sample was at 2821.9 kJ / m 2 Under the impact of water jet, the longitudinal and transverse tensile breaking strengths of the sample were 217.8 N and 168.0 N, respectively. Thanks to the low surface energy of HDPE fibers and the nonwoven structure formed by the HDPE microfiber hydroentangled web, the sample has a high hydrostatic pressure resistance of 6695.7 Pa and good air permeability and water vapor transmission rate.

[0014] 2. The HDPE microfiber material samples of this application exhibit high softness, easy folding and portability, and excellent conformability to irregular shapes. The softness scores are all above 80, the reflectivity is 94.3%, and it has an outdoor radiative cooling capacity that is 11.2 ℃ higher than that of pure cotton cloth. It can not only be used for high-strength lightweight tarpaulins, but also provide a case for the development of functional products such as sports equipment, outdoor protection and military equipment. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a schematic diagram illustrating the nonwoven process of HDPE microfiber material.

[0017] Figure 2 Electron micrographs of the surface and cross-section of samples with different water needle energies.

[0018] Figure 3 The parameters are the structural characteristics of the samples; (a) the fiber diameter distribution of the 55 g / m² sample, (b) the pore size distribution of samples with different water injection energies, and (c) the pore size distribution of samples with different unit area mass.

[0019] Figure 4 The force-displacement curves are shown during the tensile process of the sample; where (a) is the longitudinal tensile curve of the sample and (b) is the transverse tensile curve of the sample.

[0020] Figure 5 This is a diagram showing the morphology of droplets on the surface of HDPE microfiber material.

[0021] Figure 6 This is a diagram showing the waterproof and breathable properties of the sample.

[0022] Figure 7 The radiation cooling performance of the sample is shown in (a) light transmittance curve, (b) light emissivity curve, and (c) test temperature curve.

[0023] Figure 8 The softness score is the softness score of the sample; where (a) is the softness score of the sample with different water injection energies, and (b) is the softness score of the sample with different unit area mass.

[0024] Figure 9 The images show the portability, irregular shape fitting, and printing effect of the samples; (a) foldability and portability, (b) irregular shape fitting, and (c) ink adhesion. Detailed Implementation

[0025] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0026] Unless otherwise specified, the experimental methods used in the following experimental examples are conventional methods; the materials and reagents used are commercially available unless otherwise specified.

[0027] HDPE chips, grade: 5000S, density 0.95 g / m³ 3 Melting point 140~160 ℃, Beijing Yanshan Petrochemical Co., Ltd.

[0028] Example: Preparation of HDPE microfiber material I. Web Forming of HDPE Microfiber Materials Figure 1 This paper illustrates the nonwoven fabrication principle of HDPE microfiber material. The process flow is as follows: HDPE chips are heated and softened to melt into a polymer melt, which is then fed together with a solvent into a mixing vessel at a temperature of 205 °C and a pressure of 20 MPa to prepare a spinning solution with a mass fraction of 18%. The solvent is prepared by mixing dichloromethane and methanol in a mass ratio of 80:20. The spinning solution is sprayed into an atmospheric pressure environment through a depressurization chamber, where the solvent evaporates instantaneously to form HDPE microfibers. Under the action of a deflector plate, the HDPE microfibers are split, redirected, and deposited on a receiving screen to form an HDPE microfiber web.

[0029] II. Hydroentanglement of HDPE microfiber materials HDPE microfiber webs are hydroentangled using a hydroentangled web bonding system (SC-600, Changzhou Xinrenli Textile Equipment Co., Ltd.). The HDPE microfiber webs pass through multiple hydroentanglement heads and are formed into HDPE microfiber material under the impact of water jets.

[0030] Table 1 shows the main hydroentanglement process parameters.

[0031] Samples 1-10 were prepared using the above process. The following tests and characterizations of samples 1-10 are performed.

[0032] III. Testing and Characterization 3.1 Morphological Structure The surface and cross-sectional micromorphology of the samples were observed using a scanning electron microscope (JSM-IT200, JEOL Ltd., Japan) at an accelerating voltage of 5 kV. The samples underwent gold sputtering treatment before observation. From the obtained surface electron microscope images, 50 fibers were randomly selected to measure their diameter, thus obtaining the fiber diameter distribution of the samples.

[0033] Thickness: The thickness of the samples was tested using a thickness gauge (32CHQF 1030, Deqing Shengtongxin Electronic Technology Co., Ltd.) according to the test standard GB / T 24218.2-2009 Textiles - Nonwoven Fabrics - Test Methods - Part 2: Determination of Thickness. The thickness of each sample was tested 5 times; the average value was taken as the sample thickness.

[0034] Mass per unit area: The mass per unit area (100 cm²) was measured using an electronic balance (BT456A 300, Shenzhen Botu Electronic Technology Co., Ltd.) according to the test standard GB / T 24218.1-2009 Textiles - Nonwovens - Test Methods - Part 1: Determination of Mass per Unit Area. 2 The quality of the samples; each group of samples was tested 5 times, and the average value was taken.

[0035] Porosity: The porosity of the sample is calculated using formula (1). (1) In the formula: n Porosity, % p This refers to the density of HDPE fibers, in g / m³. 3 ; m Mass per unit area, g / m 2 ; δ The thickness is in meters (m).

[0037] The pore size distribution of the samples was tested using a pore size analyzer (PSM 165, Topas GmbH, Germany) according to the testing standard "ISO 4003-1997 Permeable sintered metallic materials - Determination of pore size by testing for bubbles". The test sample was a circle with a diameter of 2 cm, and the test liquid was Topar (Topas GmbH, Germany, surface tension: 16.0 mN / m).

[0038] like Figures 2-3 As shown, Figure 2 Electron micrographs of the surface and cross-section of samples with different water needle energies are shown. Figure 3 The structural characteristic parameters of the sample are shown. From... Figure 2 As shown in (a)~(e), the HDPE microfiber material prepared by the hydroentanglement process exhibits typical microfiber nonwoven structure characteristics. Circular microfibers with diameters of 1~6 μm are randomly distributed horizontally, forming a dense microfiber network. The HDPE microfiber material prepared by the hydroentanglement process further exhibits hydroentangled nonwoven structure characteristics, i.e., the microfibers are intertwined and show a certain "bundling" phenomenon, which becomes more pronounced with increasing water jet energy. Combined with Table 1, it can be seen that increasing water jet energy leads to a decrease in thickness and porosity. For 55 g / m²... 2 The sample, when the water injection energy was 1699.33 kJ / m 2 At that time, the thickness was 0.393 mm, the porosity was 85.3%, and the modal pore size was 9.5 μm. However, as the water jet energy increased to 8299.7 kJ / m³, the thickness decreased. 2 When the thickness decreased to 0.277 mm, the porosity and modal pore size decreased to 82.4% and 6.9 μm, respectively. This is because the impact of the high-energy water jet enhances the displacement transfer of the fibers, resulting in denser entanglement between the fibers, and thus reducing the volume and size of the pores between the fibers. Furthermore, the modal pore size of the HDPE ultrafine fiber material sample is inversely proportional to the mass per unit area. Figure 3 (c)). As the sample mass per unit area increases from 90 g / m², the sample mass decreases from 90 g / m². 2 Increase by 110 g / m 2 The proportion of pores with a diameter between 6 and 8 μm increased from 43.1% to 78.3%. This is because the number of fibers stacked in the thickness direction of the sample increases with the increase of mass per unit area.

[0039] 3.2 Mechanical Properties Tensile breaking strength: The tensile breaking strength of the samples was tested using an electronic fabric tensile strength tester (HD026S-100, Nantong Hongda Experimental Instrument Co., Ltd.) according to the test standard GB / T 24218.3-2010 Textiles - Test methods for nonwoven fabrics - Part 3: Determination of breaking strength and elongation at break (strip method). The samples were cut to 20 cm × 5 cm, and the tensile speed was 150 mm / min.

[0040] Bursting strength: The bursting strength of the samples was tested using a bursting strength tester (YG026MD-250, Wenzhou Fangyuan Instrument Co., Ltd.) according to the test standard GB / T 19976-2005 Determination of bursting strength of textiles - steel ball method. The samples were cut into circles with a diameter of 10 cm, and the bursting speed was 100 mm / min.

[0041] The force-displacement curves of HDPE microfiber material samples during tensile fracture are shown below. Figure 4 As shown in (a) to (b), the performance parameters are listed in Table 2. Comparing the force-displacement curves, all curves exhibit similar variation patterns. In the initial stage of stretching, the force increases non-linearly. This indicates that the microstructure of the HDPE microfiber material prepared based on hydroentanglement technology is relatively loose, making it prone to deformation and elongation under external force. As stretching progresses, the fibers of the HDPE microfiber material rearrange along the direction of force and become tensile, accompanied by some fiber breakage and slippage. In the later stage of stretching, as the number of broken and slipped fibers increases, tensile fracture occurs, and the force decreases rapidly from its highest value. It is noteworthy that the rate at which the force decreases from its highest value during transverse stretching is significantly less than that during longitudinal stretching, indicating more fiber slippage.

[0042] Table 2 Mechanical property indicators of the samples Combination Figure 4 As can be seen from Table 2, with the water needle energy increasing from 1699.3 kJ / m 2 Increased to 8299.7 kJ / m 2 The longitudinal and transverse tensile breaking strengths increased from 103.8 N and 68.9 N to 134.3 N and 84.6 N, respectively. Simultaneously, the longitudinal and transverse tensile elongation at break increased from 27.2% and 18.3% to 32.7% and 23.3%, respectively. This is because with increasing water jet energy, the interfiber entanglement becomes tighter, and the interfiber friction also increases. Similarly, the bursting strength of the sample also increased from 112.0 N to 138.7 N. Furthermore, under the condition of constant water jet energy, both the longitudinal and transverse tensile breaking strengths increased with increasing unit area mass. Specifically, when the sample unit area mass increased from 90 g / m²...2 Increased to 110 g / m 2 At that time, the longitudinal and transverse tensile breaking strengths increased to 217.8 N and 168.0 N, respectively. Finally, comparing the longitudinal and transverse tensile breaking data of the samples, it can be found that the longitudinal tensile breaking strength of all samples is significantly greater than that of the transverse tensile breaking strength. This is because during the fiber web formation process of HDPE microfiber material, the HDPE fibers are subjected to the directional force of the receiving mesh during deposition on the receiving mesh, resulting in a certain directional arrangement in the longitudinal direction. This is also the main reason why the transverse tensile breaking tensile curve of the HDPE microfiber material samples shows a longer slip length.

[0043] A rather interesting finding: 55g / m 2 The tensile breaking strength of the HDPE microfiber material sample is much higher than 45 g / m. 2 Polypropylene meltblown nonwoven material (approximately 10.2 times in the longitudinal direction and 11.3 times in the transverse direction) and 20 g / m 2 Polypropylene spunbond nonwoven material (approximately 3.1 times in the longitudinal direction and 4.5 times in the transverse direction), roughly equivalent to 70 g / m². 2 Viscose and polyester spunlace nonwoven materials.

[0044] 3.3 Waterproof and breathable performance Contact angle: The static water contact angle and rolling water contact angle of the samples were measured using a contact angle measuring instrument (SDC-350, Dongguan Shengding Co., Ltd.) according to the test standard GB / T 42694-2023 "Detection and evaluation of the anti-wetting properties of textile surfaces - contact angle and rolling angle". The measuring liquid was 5 μL of deionized water.

[0045] Hydrostatic pressure resistance: The hydrostatic pressure resistance of the samples was tested using a fully automatic hydrostatic pressure tester (YG826G, Ningbo Textile Instrument Factory, China) according to the test standard GB / T 4744 "Test and evaluation of waterproof performance of textiles - hydrostatic pressure method". The liquid seepage rate was 10 mm / s; each group of samples was tested 5 times, and the average value was taken.

[0046] Air permeability: The air permeability of the samples was tested using a fully automatic air permeability meter (YG416E-Ⅲ, Ningbo Textile Instrument Factory, China) according to the test standard GB / T 24218.15-2018 Textiles - Nonwoven Fabrics - Test Methods - Part 15: Determination of Air Permeability. The test pressure difference was 100 Pa, and the test area was 20 cm². 2 Each group of samples was tested 5 times, and the average value was taken.

[0047] Water vapor transmission rate: The water vapor transmission rate of the samples was tested using a cup-type water vapor transmission rate tester (W3, Jinan Langguang Electromechanical Technology Co., Ltd., China) according to the standard GB / T 12704.2-2009 Textiles - Test methods for moisture permeability of fabrics - Part 2: Evaporation method. The test conditions were: ambient temperature of 40 ℃; each group of samples was tested 5 times, and the average value was taken.

[0048] Excellent waterproofing and good permeability are key indicators for HDPE microfiber materials to be used in the tarpaulin field. They are commonly characterized by hydrostatic pressure resistance, air permeability and water vapor transmission rate.

[0049] Figure 5 The image shows the droplet morphology on the surface of HDPE microfiber material. As can be seen from the image, thanks to the low surface energy of the HDPE macromolecular structure and the smooth, ultrafine HDPE fiber morphology, the HDPE microfiber material sample exhibits excellent resistance to common liquids such as water, milk, tea, and cola. The water contact angle of the HDPE microfiber material sample prepared in this paper is 140±5°. Hydrostatic pressure resistance tests show that the hydrostatic pressure resistance of the prepared samples is greater than 4500 Pa, and increases with increasing water jet energy. Specifically, when the water jet energy is 1699.3 kJ / m... 2 2105.9kJ / m 2 2821.9kJ / m 2 4703.2 kJ / m 2 8299.7kJ / m 2 The hydrostatic pressures were 4557 Pa, 4688 Pa, 4779 Pa, 4804 Pa, and 4905 Pa, respectively. This is mainly because the water jet energy improved the density of the HDPE microfiber material structure. Meanwhile, as the sample's unit area mass increased from 90 g / m²... 2 Increased to 110 g / m 2 The hydrostatic pressure resistance of the sample increased to 6695.7 Pa, an improvement of approximately 9.8%.

[0050] The air permeability and water vapor transmission rate test results show that both the air permeability and water vapor transmission rate of the HDPE microfiber material sample decrease with increasing water jet energy. Specifically, when the water jet energy is 1699.3 kJ / m³, the air permeability and water vapor transmission rate decrease. 2 2105.9kJ / m 2 2821.9kJ / m 2 4703.2 kJ / m 2 8299.7 kJ / m 2At that time, the air permeability was 60.6 mm / s, 56.9 mm / s, 52.8 mm / s, 49.3 mm / s, and 45.1 mm / s, respectively, and the water vapor permeability was 2165.6 g / (m²). 2 ·24h), 2017.9 g / (m 2 ·24h), 1968.3 g / (m 2 ·24h), 1913.0 g / (m 2 ·24h), 1805.1 g / (m 2 (24h). This is because as the water jet energy increases, the water jet causes the fibers in the material to shift, making their arrangement more compact. This reduces the transport channels for water vapor, thus decreasing water vapor permeability. Additionally, an increase in the sample's unit area mass also creates stronger resistance to water vapor passage, further reducing water vapor permeability. In HDPE microfiber material samples, both air permeability and water vapor permeability decrease with increasing unit area mass. Specifically, when the unit area mass is 90 g / m², the air permeability and water vapor permeability decrease. 2 95g / m 2 100g / m 2 105g / m 2 110g / m 2 At this point, the air permeability was 48.3 mm / s, 40.8 mm / s, 39.2 mm / s, 36.2 mm / s, and 30.8 mm / s, respectively, and the water vapor permeability was 2321.2 g / (m²). 2 ·24h), 2145.9 g / (m 2 ·24h), 1819.8g / (m 2 ·24h), 1706.4 g / (m 2 ·24h), 1676.6 g / (m 2 •24h). In addition, Figure 6 The experiment demonstrates the breathability of an HDPE microfiber material sample used as a waterproof layer (test water depth 5 cm). It shows that air can easily pass through the HDPE microfiber material, forming fine and uniform bubbles in the upper water layer. This experiment indicates that the HDPE microfiber material sample has excellent application capabilities in waterproofing, outdoor sports, and other fields.

[0051] 3.4 Radiative Cooling Performance Reflectance: The reflectance of the samples was tested using a UV-Vis spectrophotometer (Color i5, X-rite, USA).

[0052] Emissivity: The absorption rate of the material in the mid-infrared band (8-14 μm) is tested using a Fourier transform infrared spectrometer. Planck's law states that the thermal absorption capacity of an object is equal to its thermal emission capacity, thus obtaining the emissivity of the material.

[0053] Radiative cooling capability: The radiative cooling capability of the sample was tested using a self-made radiative cooling test device. This device consists of a foam box wrapped in aluminum foil and a multi-channel temperature measuring instrument. A 100 cm opening was made on the surface of the foam box. 2 The sample has a square hole; during testing, the sample is placed on the surface of the foam box and covered with a layer of PE film. A multi-channel temperature meter is used to monitor temperature changes inside the box.

[0054] Figure 7 (a)~(b) show the transmittance and emissivity curves of the HDPE microfiber material samples. It can be seen that the samples prepared under different hydroentangling pressures all have high transmittance within the atmospheric transparency window, meaning they can effectively dissipate heat to the external environment. Comparing the two curves, it can be seen that 2105.9 kJ / m 2 The sample prepared by water-jet energy had a transmittance of 42.6%, which is higher than 1699.3 kJ / m³. 2 The transmittance of the sample prepared by water injection energy was 34.8%. From... Figure 7 (b) It can be seen that the sample has high reflectivity in the 350~760nm wavelength range. As the water needle energy increases from 1699.3kJ / m 2 Increased to 8299.7 kJ / m 2 The process gradually increases, until the water needle energy reaches 8299.7 kJ / m³. 2 The reflectivity can reach up to 94.3%. These results indicate that the prepared HDPE microfiber material can effectively reflect sunlight. The radiative cooling effect of the HDPE microfiber material is as follows: Figure 7 As shown in (c), the internal cavity temperature covered by the HDPE microfiber material is significantly lower than that of the pure cotton fabric in the control test, decreasing by 11.2℃, demonstrating significant radiative cooling capability. Furthermore, the reduction in water jet energy also enhances the cooling effect to some extent. 3.5 Softness The samples were tested for softness using a Phabrometer 3 (NUCYBERTE-K, USA) according to the standard GB / T 8942-2016 "Determination of Paper Softness". Each sample group was tested three times, and the average value was taken.

[0055] Figure 8 , Figure 9The images show the softness score of the HDPE microfiber material, as well as its portability, irregular shape bonding, and printing performance. It can be seen that, thanks to the morphology of the prepared HDPE microfiber web and the flexible entanglement effect of the hydroentangling process, the HDPE microfiber material exhibits high softness, foldability, portability, and excellent irregular shape bonding. Figure 8 As can be seen from (a) to (b), the softness scores of the HDPE microfiber material samples are all above 80, and can be controlled by adjusting the water jet energy and the mass per unit area. Figure 9 (a) It can be seen that the excellent softness improves the portability of HDPE microfiber materials during application. HDPE microfiber material with a spread area of ​​15×17 cm, after folding, is approximately 20 times smaller than its fully spread area. It can not only be rolled into a 3 cm ball, but also folded into a 3×5 cm rectangular handkerchief, meeting the requirements of easy folding and portability in different scenarios, and can also be used for target (…). Figure 9 (b) Provides comprehensive coverage for safety protection. Furthermore, HDPE microfiber material is also well-suited for various printing and writing applications, such as printing with pens and crayons, producing clear results. This enhances the functionality of tarpaulins in terms of aesthetics, camouflage, and safety marking.

[0056] Implementation effect analysis This application addresses the issue of poor hand feel and strong "plastic" texture of HDPE microfiber mesh, which makes it difficult to meet the commercial application requirements of high-strength, lightweight tarpaulins. An HDPE microfiber material was developed using a hydroentanglement process. Through research on the morphology, structure, and properties of the samples, the following conclusions were drawn: 1) Based on the prepared HDPE ultrafine fiber web with a diameter distribution of 1~6 μm, a uniform, dense and stable ultrafine fiber nonwoven structure can be formed under water jet impact.

[0057] 2) By adjusting the water injection energy and unit area mass, the porosity can be adjusted and controlled within the range of 82.7%~85.9% and the modal pore size within the range of 6~8 μm, thereby improving the mechanical properties; 110 g / m 2 The sample was at 2821.9 kJ / m 2 Under the impact of water jet, the longitudinal and transverse tensile fracture strengths of the sample were 217.8 N and 168.0 N, respectively.

[0058] 3) Thanks to the low surface energy of HDPE fibers and the ultra-fine fiber nonwoven structure formed by the hydroentanglement process, the sample has a high hydrostatic pressure resistance of 6695.7 Pa and good air permeability and water vapor transmission rate.

[0059] 4) The HDPE microfiber material samples exhibit high softness, easy folding and portability, and excellent conformability to irregular shapes. The softness scores are all above 80, the reflectivity is 94.3%, and it has an outdoor radiative cooling capacity that is 11.2 ℃ higher than that of pure cotton cloth. It can not only be used for high-strength lightweight tarpaulins, but also provide a case for the development of functional products such as sports equipment, outdoor protection and military equipment.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing high-density polyethylene microfiber tarpaulin, characterized in that, The steps are as follows: (1) High-density polyethylene is melted and mixed with a solvent to prepare a spinning solution, which is then sprayed under reduced pressure to form high-density polyethylene microfibers; the density of the high-density polyethylene is 0.95 g / m³. 3 Melting point 140~160 ℃; (2) The high-density polyethylene microfibers from step (1) are split and deposited on the receiving screen to form a polyethylene microfiber mesh; (3) The polyethylene microfiber mesh from step (2) is hydroentangled to obtain a high-density polyethylene microfiber tarpaulin; In step (1), the solvent is a mixture of dichloromethane and methanol in a mass ratio of 4:1; the mass fraction of the spinning solution is 10%-30%; the mixing temperature is 180-260 ℃ and the pressure is 10-50 MPa. The process parameters for hydroentangled web formation in step (3) are set as follows: main needle pressure 6-10 MPa, fabric feeding speed 1-5 m / min, and water needle energy 1699.3-8299.7 kJ / m. 2 .

2. The method for preparing high-density polyethylene microfiber tarpaulin according to claim 1, characterized in that: The energy of the water jet is 2105.9-8299.7 kJ / m³. 2 .

3. The high-density polyethylene microfiber tarpaulin prepared by the method according to any one of claims 1-2.

4. The high-density polyethylene microfiber tarpaulin according to claim 3, characterized in that: The high-density polyethylene microfiber tarpaulin has a porosity of 82.7%-85.9%, a modal pore size of 6-8 μm, and a surface density of 90-110 g / m³. 2 .

5. The high-density polyethylene microfiber tarpaulin according to claim 4, characterized in that: The high-density polyethylene microfiber tarpaulin has a water contact angle of 140±5°, a hydrostatic pressure resistance of >4500 Pa, a softness score of >80, a reflectivity of 94.3%, and an outdoor radiative cooling capacity that is 11.2 ℃ higher than that of pure cotton cloth.

6. The application of the high-density polyethylene microfiber tarpaulin according to any one of claims 4-5 in the preparation of outdoor sports and material storage.

7. The application of the high-density polyethylene microfiber tarpaulin according to any one of claims 4-5 in the preparation of military supplies.

Citation Information

Patent Citations

  • Novel antibacterial breathable fabric and preparation method thereof

    CN115074917A